A “Triple Trouble” Case of Facioscapulohumeral Muscular Dystrophy Accompanied by Peripheral Neuropathy and Myoclonic Epilepsy - Xiao-Dan Lin; Jun-Jie He; Feng Lin; Hai-Zhu Chen; Liu-Qing Xu; Wei Hu; Nai-Qing Cai; Min-Ting Lin; Ning Wang; Zhi-Qiang Wang; Guo-Rong Xu (Chinese Medical Journal, 2018)
Background: Facioscapulohumeral muscular dystrophy (FSHD) is characterized by asymmetric muscular deficit of facial, shoulder-girdle muscles, and descending to lower limb muscles, but it exists in several extramuscular manifestations or overlapping syndromes. Herein, we report a “complex disease plus” patient with FSHD1, accompanied by peripheral neuropathy and myoclonic epilepsy. Methods: Standard clinical assessments, particular auxiliary examination, histological analysis, and molecular analysis were performed through the new Comprehensive Clinical Evaluation Form, pulsed-field gel electrophoresis-based Southern blot, Multiplex Ligation-dependent Probe Amplification (MLPA), whole exome sequencing (WES), and targeted methylation sequencing. Results: The patient presented with mild facial weakness, humeral poly-hill sign, scapular winging, peroneal weakness, drop foot, pes cavus, and myoclonic epilepsy. Furthermore, electrophysiology revealed severely demyelinated and axonal injury. The muscle and nerve biopsy revealed broadly fiber Type II grouping atrophy and myelinated nerve fibers that significantly decreased with thin myelinated fibers and onion bulbs changes. Generalized sharp and sharp-slow wave complexes on electroencephalography support the diagnosis toward myoclonic epilepsy. In addition, molecular testing demonstrated a co-segregated 20-kb 4q35-EcoRI fragment and permissive allele A, which corresponded with D4Z4 hypomethylation status in the family. Both the patient's mother and brother only presented the typical FSHD but lacked overlapping syndromes. However, no mutations for hereditary peripheral neuropathy and myoclonic epilepsy were discovered by MLPA and WES. Conclusions: The present study described a “tripe trouble” with FSHD, peripheral neuropathy, and myoclonic epilepsy, adding the spectrum of overlapping syndromes and contributing to the credible diagnosis of atypical phenotype. It would provide a direct clue on medical care and genetic counseling.